2011
DOI: 10.1073/pnas.1110584108
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer (NK)–dendritic cell interactions generate MHC class II-dressed NK cells that regulate CD4+T cells

Abstract: Natural killer (NK) cells contribute to not only innate but also to adaptive immunity by interacting with dendritic cells (DCs) and T cells. All activated human NK cells express HLA-DR and can initiate MHCII-dependent CD4 + T-cell proliferation; however, the expression of MHCII by mouse NK cells and its functional significance are controversial. In this study, we show that NK-DC interactions result in the emergence of MHCII-positive NK cells. Upon in vitro or in vivo activation, mouse conventional NK cells did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 34 publications
4
99
0
Order By: Relevance
“…For one, mNK cells exhibit low levels of CD11c, 15 whereas the expression of B220 and MHC II can be up-regulated on mNK cells, at least on in vitro activation. 9,12 Secondly, several groups could not replicate the finding that IKDCs produced IFN␣, [16][17][18][19] suggesting that the IKDC preparation in the original studies 13 may have been contaminated with pDCs. Finally, 3 independent groups found that cells exhibiting the IKDC phenotype were part of the NK lineage and challenged the idea that these cells also exhibit DC properties.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…For one, mNK cells exhibit low levels of CD11c, 15 whereas the expression of B220 and MHC II can be up-regulated on mNK cells, at least on in vitro activation. 9,12 Secondly, several groups could not replicate the finding that IKDCs produced IFN␣, [16][17][18][19] suggesting that the IKDC preparation in the original studies 13 may have been contaminated with pDCs. Finally, 3 independent groups found that cells exhibiting the IKDC phenotype were part of the NK lineage and challenged the idea that these cells also exhibit DC properties.…”
Section: Introductionmentioning
confidence: 56%
“…[5][6][7] Finally, on activation, mNK cells gain the expression of additional activation markers, namely CD69, CD44, FasL, CD86, and MHC II. [8][9][10][11][12] In addition, activated mNK cells increase in size and show heightened functional properties such as an enhanced cytolytic potential and increased ability to produce cytokines. 2 Notably, activated mNK cells show a striking phenotypic resemblance to the IFN-producing killer dendritic cells (IKDCs), which were initially described as a hybrid cell type exhibiting properties of both mNK cells and plasmacytoid DCs (pDCs).…”
Section: Introductionmentioning
confidence: 99%
“…3D) lead us to address the possibility that NK cells acquire Rae-1 from target cells, rather than through de novo synthesis. We and others have recently reported that NK cells have the ability to acquire cell surface proteins from target cells in a cell-cell contact-dependent manner, referred to as trogocytosis (21,28,29). Likewise, acquisition of Rae-1 expression occurred only with direct cell-cell contact and did not occur on NK cells cultured with RMA/Rae-1δ in Transwell plates (Fig.…”
Section: Nk Cell Deathmentioning
confidence: 98%
“…NK cells were prepared from mouse splenocytes as described previously (28). In brief, splenocytes were incubated with anti-CD4 mAb (clone GK1.5) and anti-CD8 mAb (clone 53-6.7), followed by magnetic beads coated with goat anti-mouse Ig and goat anti-rat Ig Abs (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Acquisition of MHC-I by NK cells from tumor cells leads to a reduced NK cytotoxic function (41). Acquisition of MHC-II from DCs via trogocytosis has been shown in CD4 T cells, NK cells, DCs, macrophages, and lymph node stromal cells (28,(42)(43)(44)(45). MHC-II-dressed recipient cells either stimulate or suppress T cells, perhaps depending on the expression and acquisition of costimulatory molecules (28).…”
Section: Cd11cmentioning
confidence: 99%